Endonasal endoscopic resection of ossifying fibroma involving the ethmoid sinus, orbit and anterior skull base: case report and literature review - Jurlina, M. (Acta Otorhinolaryngol Ital, 2016)
Ossifying fibroma is a benign fibro-osseous tumour that rarely involves the ethmoid sinuses and orbit. It is classified as a benign fibroosseous lesion, a term that is synonymous with a variety of lesions reported in the literature. Recurrence rate with deleterious effects in cases of extramandibular ossifying fibroma is the impetus for open en bloc resection of the tumour. Continuously evolving techniques in endonasal endoscopic sinus surgery has rendered resection of large benign sinonasal and cephalonasal tumours possible. The authors report a case of ossifying fibroma involving the ethmoid sinus, orbit and anterior skull base in a 65-year-old previously healthy woman completely resected by endonasal endoscopic sinus surgery. The patient was free from postoperative complications and was dismissed from hospital on the sixth postoperative day. At present, the patient is disease-free at a regular five-year postoperative follow-up. Endonasal endoscopic resection of sinonasal ossifying fibromas is an excellent therapeutic option when performed by a surgeon experienced in endoscopic sinonasal surgery. The advantages of an endonasal endoscopic approach include direct visualization, enhanced visibility and magnification resulting in decreased intraoperative and postoperative morbidity. Aesthetic outcome is excellent in the absence of facial scars.